Storytelling on Oral Grounds: Viewpoint Alignment and Perspective Taking in Narrative Discourse - van Krieken, Kobie; Sanders, José (Frontiers in Psychology, 2021)
In this paper we seek to explain the power of perspective taking in narrative discourse by turning to research on the oral foundations of storytelling in human communication and language. We argue that narratives function through a central process of alignment between the viewpoints of narrator, hearer/reader, and character, and develop an analytical framework that is capable of generating general claims about the processes and outcomes of narrative discourse while flexibly accounting for the great linguistic variability both across and within stories. The central propositions of this viewpoint alignment framework are that the distance between the viewpoints of participants in the narrative construal– narrator, character, reader – is dynamic and regulated by linguistic choices as well as contextual factors. Fundamentally, viewpoint alignment is grounded in oral narrative interaction, and from this conversation transferred to the written narrative situation, varying between demonstration and invasion of the narrative subjects, and guiding readers’ route of processing the narrative (experiential versus reflective). Our claim is that variations in viewpoint alignment are functional to the communicative context and intended outcomes of narratives. This is illustrated with the analysis of a corporate journalistic narrative that comprises both interactional and non-interactional aspects of storytelling. The concept of viewpoint alignment further explains the oral fundaments of narrative discourse in conversational storytelling, and poses new questions on the relation between the dynamic processing of stories on the one hand and their static outcomes on the other.